To the question of use of health fitness in the process of professional and applied physical preparation of student youth - Kashuba, Vitaliy; Asaulyuk, Inna; Dyachnko, Anna (Journal of Education, Health and Sport, 2017)
Topicality. The distinctive feature of using the "Functional Loops TRX" simulator is safety – performing functional exercises, you work with the weight of your body, which does not damage joints and ligaments; further, the spine experiences almost no load; while balancing, even deep muscle-stabilizers, which are almost impossible to work on with the usual simulators, are involved. The high performing efficiency of the musician ensures the presence of a range of important qualities. The structure of the qualities includes: performing technique, reliability, artistry in a concert performance and, not less important, the development of personal physical qualities.These features testify to the topicality of developing physical qualities in the process of implementing health fitness means in the framework of professional and applied physical training as part of education to achieve a high level of health, nurture a positive attitude to physical education and sports activities, and take into account the specific features of the future specialty.Research objectives. To systematize the results of practical experience using modern fitness technologies in the practice of physical education of students and to characterize the training load parameters when using the "Functional Loops TRK" simulator with students of specialty "Music ".Research results. The authors are unanimous in the opinion that to improve the quality of the organization of the process of physical education in educational institutions, it is necessary to conduct targeted work, which, in the first place, should encompass diagnostics of physical preparedness of students with the subsequent adoption of pedagogical measures. The complexes of exercises with the use of the "Functional Loops TRK" simulator were developed for introducing the data of innovative technologies of health fitness into the practice of students of specialty "Music".Conclusions. The complexes of physical exercises using the "Functional Loops TRX" simulator for students of specialty "Music" are developed. The complex includes exercises that enable improvement of joint mobility, development of strength endurance and coordination abilities of the deep muscles of the musculoskeletal system.Prospects for further research will be related to the development of technology for correcting the physical condition of students of specialty “Music” in the process of physical education.